European legal cultures in transition - Grødeland, Åse B.; Miller, William Lockley 1943- (Cambrige Univ. Press, 2015)
"Are national legal cultures in Europe converging or diverging as a result of the pressures of European legal integration? Åse B. Grødeland and and William L. Miller address this question by exploring the attitudes and perceptions of the general public and law professionals in five European countries: England, Norway, Bulgaria, Poland and the Ukraine. Presenting new findings, they challenge the established view that ordinary citizens and people working professionally with the law have different legal cultures. Their research in fact reveals that the attitudes of citizens in Eastern and Western Europe towards 'law-in-principle' are remarkably similar, whereas perceptions of 'law-in-practice' differ by country and often correlate with GDP per capita and country ranking in rule of law indices. Grødeland and Miller's innovative methodological approach will appeal to both experts and non-experts with an interest in legal culture, European integration, or European elite and public opinion"..
Includes bibliographical references and index
Keywords: LAW / Comparative; Recht; Law -- Europe; Rechtskultur; Rechtssystem; Europa